Welcome to the suck : narrating the American soldier's experience in Iraq - Peebles, Stacey L. (Stacey Lyn), 1976- (Cornell University Press, 2011)
"Stacey Peebles examines the growing body of contemporary war stories in prose, poetry, and film that speak to the American soldier's experience in the Persian Gulf War and the Iraq War. Stories about war always encompass ideas about initiation, masculinity, cross-cultural encounters, and trauma. Peebles show us how these timeless themes find new expression among a generation of soldiers who have grown up in an era when it has been more acceptable than ever before to challenge cultural and societal norms, and who now have unprecedented and immediate access to the world away from the battlefield through new media and technology"--Jacket.